A Kinase and a Glycosylase Catabolize Pseudouridine in the Peroxisome to Prevent Toxic Pseudouridine Monophosphate Accumulation - Chen, Mingjia; Witte, Claus-Peter (The Plant cell, 2020)
Pseudouridine (Ψ) is a frequent nucleoside modification that occurs in both noncoding RNAs and mRNAs. In pseudouridine, C5 of uracil is attached to the Rib via an unusual C-glycosidic bond. This RNA modification is introduced on the RNA by site-specific transglycosylation of uridine (U), a process mediated by pseudouridine synthases. RNA is subject to constant turnover, releasing free pseudouridine, but the metabolic fate of pseudouridine in eukaryotes is unclear. Here, we show that in Arabidopsis ( ), pseudouridine is catabolized in the peroxisome by (1) a pseudouridine kinase (PUKI) from the PfkB family that generates 5'-pseudouridine monophosphate (5'-ΨMP) and (2) a ΨMP glycosylase (PUMY) that hydrolyzes ΨMP to uracil and ribose-5-phosphate. Compromising pseudouridine catabolism leads to strong pseudouridine accumulation and increased ΨMP content. ΨMP is toxic, causing delayed germination and growth inhibition, but compromising pseudouridine catabolism does not affect the Ψ/U ratios in RNA. The bipartite peroxisomal PUKI and PUMY are conserved in plants and algae, whereas some fungi and most animals (except mammals) possess a PUMY-PUKI fusion protein, likely in mitochondria. We propose that vacuolar turnover of ribosomal RNA produces most of the pseudouridine pool via 3'-ΨMP, which is imported through the cytosol into the peroxisomes for degradation by PUKI and PUMY, a process involving a toxic 5'-ΨMP intermediate.